2020
DOI: 10.1002/adpr.202000089
|View full text |Cite
|
Sign up to set email alerts
|

Sensitizing Full‐Spectrum Lanthanide Luminescence within a Semiconductor CaZnOS Host

Abstract: Lanthanide ions are appealing for luminescence applications due to their sharp and tunable emission lines spanning the whole spectral range. However, the parity‐forbidden nature of the electronic transition in lanthanide ions typically results in ineffective excitation processes, which is a major obstacle to practical applications of lanthanide‐based luminescent materials. Herein, a general method to sensitize lanthanide luminescence within a semiconductor host of CaZnOS is developed. Efficient energy transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Assumedly, ML could be more susceptible to temperature variations as compared to PL because energy transfer to the dopants has to compete with additional energy dissipation channels in the host. [ 44 ] The intensity ratio of the two green bands ( 2 H 11/2 , 4 S 3/2 → 4 I 15/2 ) could provide temperature information; it will be evaluated later. The intensity ratio of the red ( I red , 4 F 9/2 → 4 I 15/2 ) and the green band ( I green , 4 H 11/2 , 4 S 3/2 → 4 I 15/2 ) is also useful, because it is independent of thermal quenching and excitation intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Assumedly, ML could be more susceptible to temperature variations as compared to PL because energy transfer to the dopants has to compete with additional energy dissipation channels in the host. [ 44 ] The intensity ratio of the two green bands ( 2 H 11/2 , 4 S 3/2 → 4 I 15/2 ) could provide temperature information; it will be evaluated later. The intensity ratio of the red ( I red , 4 F 9/2 → 4 I 15/2 ) and the green band ( I green , 4 H 11/2 , 4 S 3/2 → 4 I 15/2 ) is also useful, because it is independent of thermal quenching and excitation intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, tunable ML spanning visible and NIR has been realized with high brightness and repeatability (Figure b). We demonstrated that the lanthanide-doped CaZnOS crystals can further accommodate Mn 2+ or Cu + dopants owing to the Zn 2+ sites, , resulting in tunable multimode luminescence by excitation of X-ray, UV, and NIR photons as well as mechanical action, respectively. Notably, CaZnOS can form a heterojunction with ZnS due to their structural similarity, which enhances ML as a result of band offset …”
Section: Emerging Host Materials For MLmentioning
confidence: 99%
“…Compared to other NIFP materials, the optical properties of near-infrared (NIR) lanthanide complexes, unlike that of organic fluorophores and semiconductor nanoparticles, possess amazing complementary superiorities, which have become a research hotspot . In terms of Ln-MOFs powered by tunable luminescence properties, long luminescent lifetimes, and forceful energy transfer ability, the assistance of a sensitizer is highly effective for realizing the enhancement luminescence of Ln 3+ and spectrum control. The reported sensitizers include Ln 3+ , semiconductors, , organic matters, and so on. Among them, sensitization between Ln 3+ is the most common.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced luminescence effect stems from the energy transfer of the sensitizer and luminescent Ln 3+ . One situation is that the 4f electronic layer of optically inert lanthanide metal counterions such as La 3+ , Gd 3+ , and Y 3+ is in a stable state of full or half-empty, and their low probability of trapping electron results in that the ligand cannot effectively transfer energy to them but only to luminous ions such as Eu 3+ and Tb 3+ , thus enhancing the characteristic fluorescence of Eu 3+ and Tb 3+ . Otherwise, luminescent Ln 3+ ions can also implement sensitization by embedding in a subjectival host in the form of doping, , in which the sensitized ion and doped sensitizer have similar ion radius and configuration of extra-nuclear electron, which may further strengthen the effect of the doped ions in synergistic energy transfer, such as the sensitization of Tb 3+ to Eu 3+ and Ce 3+ to Tb 3+ . Based on this preponderance, we speculated that it is easier to achieve sensitization between Eu 2+ and Eu 3+ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation